A quantitative model for disruptions mitigation in a supply chain considering random capacities and disruptions at supplier and retailer. Issue 4 (2nd October 2018) - Rahman, Md. Habibor; Rifat, Mustafa; Azeem, Abdullahil; Ali, Syed Mithun
Abstract: Effective response and recovery from disruptions are vital to achieving the supply chain objectives. This study aims to formulate a quantitative model for mitigating disruptions in a supply chain. An inventory model has been developed for a manufacturer with one supplier and one retailer by considering random capacity of the supplier and random availability of both the supplier and the retailer assuming zero delivery lead time. Backorders are allowed and it has two parts – unit dependent and both unit and time-dependent. This study suggests an optimal order quantity and a reordering point so that the average cost per cycle gets minimized. A genetic algorithm is used to solve the proposed inventory model. The applicability of the proposed model has been tested using a numerical example. Finally, sensitivity analysis is performed to examine the robustness of the model.